Platelet Phagocytosis via P-selectin Glycoprotein Ligand 1 and Accumulation of Microparticles in Systemic Sclerosis - Manfredi, Angelo A.; Ramirez, Giuseppe A.; Godino, Cosmo; Capobianco, Annalisa; Monno, Antonella; Franchini, Stefano; Tombetti, Enrico; Corradetti, Sara; Distler, Jörg; Bianchi, Marco E.; Rovere-Querini, Patrizia; Maugeri, Norma (Arthritis and Rheumatology, 2021)
Objective It is unclear why activated platelets and platelet-derived microparticles (MPs) accumulate in the blood of patients with systemic sclerosis (SSc). This study was undertaken to investigate whether defective phagocytosis might contribute to MP accumulation in the blood of patients with SSc. Methods Blood samples were obtained from a total of 81 subjects, including 25 patients with SSc and 26 patients with stable coronary artery disease (CAD). Thirty sex- and age-matched healthy volunteers served as controls. Studies were also conducted in NSG mice, in which the tail vein of the mice was injected with MPs, and samples of the lung parenchyma were obtained for analysis of the pulmonary microvasculature. Tissue samples from human subjects and from mice were assessed by flow cytometry and immunochemical analyses for determination of platelet-neutrophil interactions, phagocytosis, levels and distribution of P-selectin, P-selectin glycoprotein ligand 1 (PSGL-1), and HMGB1 on platelets and MPs, and concentration of byproducts of neutrophil extracellular trap (NET) generation/catabolism. Results Activated P-selectin+ platelets and platelet-derived HMGB1+ MPs accumulated in the blood of SSc patients but not in the blood of healthy controls. Patients with CAD, a vasculopathy independent of systemic inflammation, had fewer P-selectin+ platelets and a negligible number of MPs. The expression of the receptor for P-selectin, PSGL-1, in neutrophils from SSc patients was significantly decreased, raising the possibility that phagocytes in SSc do not recognize activated platelets, leading to a failure of phagocytosis and continued neutrophil release of MPs. As evidence of this process, activated platelets were not detected in the neutrophils from SSc patients, whereas they were consistently present in the neutrophils from patients with CAD. HMGB1+ MPs elicited generation of NETs, which were only detected in the plasma of SSc patients. In mice, P-selectin-PSGL-1 interaction resulted in platelet phagocytosis in vitro and influenced the ability of MPs to elicit NETs, endothelial activation, and migration of leukocytes through the pulmonary microvasculature. Conclusion The clearance of activated platelets via PSGL-1 limits the undesirable effects of MP-elicited neutrophil activation. This balance is disrupted in patients with SSc. Its reconstitution might curb vascular inflammation and prevent fibrosis.
CRIS-Team WoS Importer:2021-12-31